Anomalous decay of pion and eta at finite density - Costa, P. (2003)
We study the anomalous decays [pi]0, [eta]-->[gamma][gamma] in the framework of the three-flavor Nambu-Jona-Lasinio [NJL] model, in the vacuum and in quark matter in [beta]-equilibrium. It is found that the behavior of the relevant observables essentially reflects a manifestation of the partial restoration of chiral symmetry, in nonstrange and strange sectors. The probability of such decays decreases with density, showing that anomalous mesonic interactions are significantly affected by the medium.